2022
DOI: 10.3389/fnagi.2022.1002281
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between adult subventricular neurogenesis and Alzheimer’s disease: Pathologic roles and therapeutic implications

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease that is characterized by irreversible cognitive declines. Senile plaques formed by amyloid-β (Aβ) peptides and neurofibrillary tangles, consisting of hyperphosphorylated tau protein accumulation, are prominent neuropathological features of AD. Impairment of adult neurogenesis is also a well-known pathology in AD. Adult neurogenesis is the process by which neurons are generated from adult neural stem cells. It is closely related to various functions, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…Accumulation of Aβ affected impaired adult neurogenesis in AD ( 11 , 13 ). Thus, to investigate Aβ accumulation with AD progression in the SVZ and caudate putamen, we performed the immunohistochemical analysis using an anti-4G8 antibody, which is an Aβ-specific marker, in 2-, 4-, 8-, and 11-month-old 5XFAD mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of Aβ affected impaired adult neurogenesis in AD ( 11 , 13 ). Thus, to investigate Aβ accumulation with AD progression in the SVZ and caudate putamen, we performed the immunohistochemical analysis using an anti-4G8 antibody, which is an Aβ-specific marker, in 2-, 4-, 8-, and 11-month-old 5XFAD mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One study using multimodal magnetic resonance imaging reported that the mean diffusivity in the SVZ was changed in mild cognitive impairment compared to healthy controls and increased with the severity of the disease ( 10 ). A recent study reported that Aβ and tau depositions and dysfunction of lipid metabolism can impair adult SVZ neurogenesis in early stages of AD ( 11 ). In particular, adult neurogenesis is altered before the formation of Aβ plaques in an AD mouse model ( 12 ), and a recent study has reported that intracellular Aβ accumulation in neural stem cells impairs adult neurogenesis ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interferon signaling is also spatially resolved, however. Sites of adult neoneurogenesis have been shown to be more vulnerable to aberrant IFN-I signaling, including the subventricular zone (SVZ) and the hippocampus ( Blank and Prinz, 2017 ; Viengkhou and Hofer, 2023 ) – sites furthermore important in the setting of Alzheimer’s disease ( Kim et al, 2022 ), with the EOCN potentially affected in early or preclinical stages ( Roberts et al, 2016 ; Yahiaoui-Doktor et al, 2019 ; Tian et al, 2022 ; Xiao et al, 2023 ). This concept appears to account for this specific aspect of COVID-19 neuropathology, where microgliosis ( Poloni et al, 2021 ) and a decrease in adult human neoneurogenesis are combined ( Stępień et al, 2023 ).…”
Section: Are Sars-cov-2-introduced Perturbations In Type I Interferon...mentioning
confidence: 99%
“…Notably, aside from disease-associated microglia (DAM), IFN-I expressing microglia have also been shown to enhance neurodegeneration as well as the infiltration of the SVZ by T helper cells ( Zhang et al, 2023 ). The interaction between microglia and T cells in the SVZ are state specific, with an apparent infiltration occurring with advanced age ( Kim et al, 2022 ), when basal IFN-I responses are also altered ( Baruch et al, 2014 ). Excessive exposure to the secretion of type I interferon by the microglia either in vitro or in vivo can lead to derangement of functional neuronal maturation ( Hattori et al, 2020 ).…”
Section: Are Sars-cov-2-introduced Perturbations In Type I Interferon...mentioning
confidence: 99%
“…Therefore, this experiment used the advantages of ultrasound to probe the brain structure of experimental animals. In neurological diseases, drugs delivered to several brain regions, such as the olfactory bulb, lateral ventricles, cerebral cortex, striatum, and hippocampus, can affect cognitive function and behavior in different neurodegenerative diseases 12,13 . Under the guidance of ultrasound, the location of a puncture could be determined, and the structure of the cerebral cortex, hippocampus, lateral ventricle, and striatum of rats could be observed, which provides a theoretical basis for the application of ultrasound in animal research.…”
Section: Introductionmentioning
confidence: 99%